Differential cognitive and clinical improvements in Schizophrenia and bipolar disorder following hospitalization: A comparative analysis based on the Clock Drawing Test - Ahmad Pirani; Atiye Sarabi-Jamab; Faeze Bostan; Razieh Salehian; Mehran Ilaghi; Ali Aledavoud; Seyed Vahid Shariat; Fatemeh Sadat Mirfazeli (PLoS ONE, 2025)
Background Schizophrenia (SCZ) and bipolar disorder with psychotic features (BDP) are psychiatric disorders with significant impact on affected individuals. However, research comparing cognitive impairments between these groups is limited. This study aimed to evaluate the changes in cognitive function based on the Clock Drawing Test (CDT) among hospitalized SCZ and BDP patients and its association with positive and negative symptoms. Methods This cross-sectional study enrolled 84 Iranian patients (42 SCZ, 42 BDP, 51 male and 33 female) aged 42.85 (±11.51), ranging from 20 to 65 years old, from two psychiatric hospitals in Iran. The Positive and Negative Syndrome Scale (PANSS), Clinical Global Impression (CGI) scale and CDT were administered during the admission and discharge of patients. Within-group and between-group changes were analyzed using paired t-tests for pre-post comparisons and multiple regression was used to assess predictive factors of changes in cognitive and symptom changes. Results Both groups showed cognitive and clinical improvements at discharge, but changes were more pronounced in the BDP group for CDT, PANSS-positive symptoms, and CGI. However, PANSS-negative symptoms improved more in SCZ patients. No correlations existed between changes in CDT and positive and negative symptoms in either of the groups. Conclusion While both groups exhibited cognitive and clinical improvements following hospitalization, patients with SCZ showed relatively less improvement in the CDT compared to those with BDP. These findings suggest that cognitive recovery may follow a different trajectory in SCZ, independent of changes in positive and negative symptoms but related to the initial cognitive profile. However, given that the CDT is a screening tool rather than a comprehensive cognitive assessment, these results should be interpreted with caution. Future research should incorporate broader neurocognitive assessments to better understand the cognitive trajectories of these populations.